MENGAPLIKASIKAN TEHNIK POHON UNTUK MENINGKATKAN KOSA KATA SISWA KELAS VII MTS NEGERI 1 PALU - Ernawatit, Ernawatit; Nadrun, Nadrun; Omolu, Fikriani A. A. (Universitas Muhammadiyah Palu, 2020)
This research was conducted at the Seventh Grade students of MTs. Negeri 1 Palu. It was quasi experimental research as design. The sample was Seventh B and Seventh C consisting 30 students each. The data was collected from the Test (Pre-test and Post-test). The findings of the research shows that the application of tree technique can increase studentsâ€™ Vocabulary mastery. The result of pretest shows the average score of the experimental group is 65.13, while the average score of the control group is 72.92. Meanwhile, the result of the posttest reveales that the average score of the experimental group is 74.59, while in the average score of the control group is 68.06. The difference in vocabulary scores of the experimental group and the control group is 6.53. It shows that the average score of the experimental group is higher than the control group. Using t-test, the calculatedÂ t-value is found 7.287. It is higher than the t-table value which is 2.019. From the calculation, it can be stated that there is a significant difference between the experimental group and the control group. The researcher concludes that the students can increase their vocabulary mastery through the use of tree technique. Furthermore, with this technique the students are able to explore their new vocabularies.Key terms: Tree Technique, Vocabulary Mastery, Quasi Experimental.